2010
DOI: 10.1089/gtmb.2010.0023
|View full text |Cite
|
Sign up to set email alerts
|

Association of the G894T Polymorphism of the Endothelial Nitric Oxide Synthase Gene with Diabetic Foot Syndrome Foot Ulcer, Diabetic Complications, and Comorbid Vascular Diseases: A Turkish Case–Control Study

Abstract: G894T polymorphism of eNOS gene was not associated with foot ulcer and diabetic complications, except in the presence of atherosclerotic heart disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 33 publications
0
10
0
3
Order By: Relevance
“…In a study by Corapciogluin on 97 Turkish diabetic foot ulcer patients and 102 controls, it was reported a significant association between eNOS alleles in patients with atherosclerotic heart disease, because GT-TT alleles were significantly higher than the GG alleles [29].…”
Section: Discussionmentioning
confidence: 97%
“…In a study by Corapciogluin on 97 Turkish diabetic foot ulcer patients and 102 controls, it was reported a significant association between eNOS alleles in patients with atherosclerotic heart disease, because GT-TT alleles were significantly higher than the GG alleles [29].…”
Section: Discussionmentioning
confidence: 97%
“…Another study by Demet et al, that measured the association between G894T polymorphism of the eNOS gene and DFU, in Turkish diabetic patients, concluded that there was no significant association between G894T polymorphism and DFU. This finding suggested that eNOS gene polymorphisms may not be associated with early-onset diabetic microangiopathy (Corapcioglu et al, 2010).…”
Section: The G894t Polymorphism Of the Endothelial Nitric Oxide Synthmentioning
confidence: 91%
“…При дослідженні генотипів eNOS у турецького населення з діабетичними судинними ускладненнями виявлено, що між генотипами контролю та хворими ЦД типу 2 не було суттєвих відмінностей у співвідношенні алелей G894T гена eNOS. Між групами з ускладненнями діабету та без таких значне розходження було знайдено тільки в розподілі алелей у пацієнтів із супутньою атеросклеротичною хворобою серця, чиї GT-TT алелі були значно вище, ніж алелі GG (р = 0,004) [17].…”
Section: рисунок 1 поліморфні варіанти гена ендотеліальної No-синтазиunclassified
“…У дослі-дженні, в якому вивчали поліморфізм G894T гена еNOS у хворих на ЦД типу 2, ускладнений ДСПН, виявлена асоціація G894T варіанта гена еNOS з прогресуванням діабетичної нейропатії та серцево-судинними захворюваннями. Встановлено, що даний поліморфізм може моделювати перебіг і тяжкість діабетичної нейропатії [17]. У дослідженнях, проведених у населення Південної Індії, було визначено, що поява мутантного генотипу (еNOS-894 GT/TT) була вищою (75 %) у хворих на ЦД типу 2 порівняно з контрольною групою (29,37 %) [25].…”
Section: результатиunclassified